Amelanotic melanoma of the root of the tongue in a canine patient treated by electrochemotherapy - Maglietti, Felipe Horacio (2014)
Background: Electrochemotherapy is a novel tumor treatment routinely used for cutaneous and subcutaneous tumors in human patients in the European Union since 2006. Here we used it to treat an amelanotic melanoma of the root of the tongue in a canine patient. Case Presentation: The patient was a 9 year-old, female, Golden Retriever, dehydrated, cachectic and in a bad general condition due to the difficulty in eating and drinking provoked by the tumor. The procedure was performed with general anesthesia, with intravenous administration of bleomycin, and went uneventful. The only adverse effect was an important swelling of the tongue which lasted 2 days and was controlled with non-steroidal anti-inflammatory drugs. Results and Conclusion: A good local control of the disease was achieved with a 83% reduction of the tumor mass, at day 21 after a single treatment. On the 33rd day the patient died after a digestive hemorrhage not related to the treatment. Electrochemotherapy was found a good approach to locally control the disease. The swelling of the tongue was an important side effect which has to be taken into account when treating this organ, and should be controlled with medication.